Industrial Wastes in Soil Improvement. (15th September 2011) - Rama Subbarao, G. V.; Siddartha, D.; Muralikrishna, T.; Sailaja, K. S.; Sowmya, T.
Abstract : Soil existing at a particular site may not be appropriate for construction of engineering structures. The present study made an attempt to enhance the geotechnical properties of a soil replaced with industrial wastes having pozzolanic value like rice husk ash (RHA) and fly ash (FA). Soil is replaced with RHA in 2%, 4%, and 6% to dry weight of soil. It is observed that soil replaced with 4% RHA is the optimum for the soil used in this study from geotechnical point of view. To know the influence of fly ash, soil is further replaced with 4% FA along with 4% RHA. It is found that results of soil replacement by both RHA and FA proved to be soil modification and not the improvement. Hence, a cost-effective accelerator like lime is used for further replacing the above soil-4%, RHA-4% FA mix. The optimum lime content is found to be 4%.